On the role of the engrailed+ gene in the internal organs of Drosophila. - Lawrence, P A (1984)
Our purpose is to assess the effects of lethal alleles of engrailed on cells of the internal organs of Drosophila. Using nuclear transplantation we make mosaic flies that contain regions made by engrailed-lethal cells that are genetically labelled. We find that engrailed-lethal cells cause defects in some parts of the epidermis and central nervous system. Most of the internal organs of the fly are assessed and of those, all organs and tissues derived from the endoderm or the splanchnic and somatic mesoderm are normal; flies carrying engrailed-lethal cells in large areas of these organs are viable. We postulate that segments of the mesoderm are single units of cell lineage and that, unlike the ectoderm, they are not subdivided into anterior and posterior compartments.